Tanggung Jawab Hukum dalam Bisnis: Strategi Kepatuhan untuk Keberlanjutan Usaha - Ansah, Muhammad Ariel Adi; Saputra, Gofin Listian Agus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Legal responsibility in business is a fundamental aspect that ensures the company's operations comply with applicable regulations. This article discusses legal compliance strategies in the context of business sustainability in Indonesia, focusing on corporate law principles, business ethics, as well as taxation and labor regulations. Using a qualitative approach and literature review from Abdullah Zailani's works, this article highlights the importance of integrating law and ethics in business practices to create a fair and transparent economic system. A case study of local SMEs in Solo is used as a practical example of implementing legal business responsibilities.